2012
DOI: 10.3382/ps.2011-01735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-protein diets and single sex on production performance, plasma metabolites, digestibility, and nitrogen excretion in 1- to 48-day-old broilers

Abstract: Two experiments were conducted to investigate the effect of low-CP diets supplemented with crystalline amino acids, according to an ideal amino acid ratio, on the performance, plasma metabolites, nutrient digestibility, nitrogen balance, and water intake in male and female chickens from 1 to 48 d of age using a 4-phase feeding program: prestarter (1-7 d), starter (8-21 d), grower (22-35 d), and finisher (36-48 d). Three experimental diets were formulated for each phase: a control diet with a CP level of 24.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
39
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 41 publications
15
39
2
1
Order By: Relevance
“…This result is in agreement with that reported by (Waldroup et al, 1976;Leeson, 1986;Cheng et al, 1997Cheng et al, , 1999) who emphasised the importance of maintaining optimal amino acid balance under hot weather conditions. The present findings support those of Swennen et al (2006) and Hernández et al (2012) who showed that birds fed unfortified low-CP diets had lower serum UA. This is expected because UA is the end product of protein catabolism in chickens.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result is in agreement with that reported by (Waldroup et al, 1976;Leeson, 1986;Cheng et al, 1997Cheng et al, , 1999) who emphasised the importance of maintaining optimal amino acid balance under hot weather conditions. The present findings support those of Swennen et al (2006) and Hernández et al (2012) who showed that birds fed unfortified low-CP diets had lower serum UA. This is expected because UA is the end product of protein catabolism in chickens.…”
Section: Discussionsupporting
confidence: 82%
“…There is no clear explanation for the discrepancies. However, the inconsistencies could be associated with factors such as CP level in the control diet, and concentration of supplemented AA (McGill et al, 2012b), energy level (Sklan and Plavnik, 2002), gender (Hernández et al, 2012), and age of chickens (Deschepper and DeGroote, 1995). Interestingly, in our study birds fed NC+EAA+NEAA diet had significantly poorer FCR comparable with those provided Amino acids profile for tropical climate NC+NEAA diet.…”
Section: Discussionsupporting
confidence: 45%
“…On the other hand, Kamran et al (2008), observed that BW and FCR linearly worsed and feed intake increased when dietary energy and protein were reduced. These results are in agreement with those of Nguyen et al (2012), who showed that high energy and protein levels resulted in better FCR; and with results by Hernández et al (2012), who verified that low protein levels led to worse FCR. In the present experiment, the BW of male broilers fed LF and housed at high density was reduced, consistently with the results of Tong et al (2012).…”
Section: Resultssupporting
confidence: 82%
“…On the one hand, feeding low protein diets on broiler is important, because it will reduce production costs and pollution levels caused by excessive nitrogen excretion (El-Hakim et al, 2009;Hernandez et al, 2012), lower levels of air and water pollution, lower the conversion of nitrogen to ammonia gas and increase nitrogen digestibility efficiency (El-Hakim et al, 2009;Nahm, 2007) and lower levels of stress caused by heat stress (Furlan et al, 2004). Hernandez et al (2012) found that the reduction of protein levels by 1.5% or 3.0% decrease nitrogen excretion into the environment of 9.5 and 17% in male broilers, and 11.8 and 14.6% in females. On the other hand, feeding low protein diets increased fat deposition in broiler chickens (Farahdiba et al, 2011;Jlali et al, 2012;Labussiere et al, 2008: Pesti, 2009Wood et al, 2004) .…”
Section: Introductionmentioning
confidence: 99%